Soil bacterial communities of paddy are dependent on root compartment niches but independent of growth stages from Mollisols of Northeast China - Liu, Kai; Wang, Qiuju; Sun, Minglong; Gao, Shiwei; Liu, Qing; Shan, Lili; Guo, Junxiang; Bian, Jingyang (Frontiers in Microbiology, 2023)
Deep insights into adhering soil of root zones (rhizosphere and rhizoplane) microbial community could provide a better understanding of the plant-microbe relationship. To better understand the dynamics of these microbial assemblies over the plant life cycle in rhizodeposition along rice roots. Here, we investigated bacterial distribution in bulk, rhizosphere and rhizoplane soils at tillering, heading and mature stage, from rice (Oryza sativa) fields of the Northeast China. Our results revealed that soil bacterial α-diversity and community composition were significantly affected by root compartment niches but not by temporal change. Compared to rhizoplane soils in the same period, bulk in the heading and rhizosphere in the mature had the largest increase in Shannon’s index, with 11.02% and 14.49% increases, respectively. Proteobacteria, Chloroflexi, Bacteroidetes and Acidobacteria are predominant across all soil samples, bulk soil had more phyla increased across the growing season than that of root related-compartments. Deterministic mechanisms had a stronger impact on the bacterial community in the compartments connected to the roots, with the relative importance of the bulk soil, rhizoplane and rhizosphere at 83%, 100%, and 56%, respectively. Because of ecological niche drivers, the bacterial networks in bulk soils exhibit more complex networks than rhizosphere and rhizoplane soils, reflected by more nodes, edges, and connections. More module hub and connector were observed in bulk (6) and rhizoplane (5) networks than in rhizosphere (2). We also detected shifts from bulk to rhizoplane soils in some functional guilds of bacteria, which changed from sulfur and nitrogen utilization to more carbon and iron cycling processes. Taken together, our results suggest distinct bacterial network structure and distribution patterns among rhizosphere, rhizoplane and bulk soils, which could possibly result in potential functional differentiation. And the potential functional differentiation may be influenced by plant root secretions, which still needs to be further explored.